Analysis of the polymorphisms in non-homologous DNA end joining (NHEJ) gene Ku70 and Ligase IV in sporadic breast cancer in women - Sobczuk, Anna; Smolarz, Beata; Romanowicz, Hanna; Zadrożny, Marek; Baszczyński, Jakub; Westfal, Bogusław; Pertyński, Tomasz (Polish Journal of Pathology, 2010)
Purpose: Breast cancer is one of the major killers worldwide. Aberrant double-stranded break (DSB) repair leads to genomic instability, which is a hallmark of malignant cells. Double-stranded breaks are repaired in two pathways: homologous recombination (HR) and non-homologous DNA end joining (NHEJ). It is not known whether these repair pathways are affected in sporadic breast tumours. Material and methods: In the present work the distribution of genotypes and frequency of alleles of the Ku70, A46922G (rs132793) polymorphism and Ligase IV, A6008G (Ile591Val) (rs2232641) polymorphism in breast cancer women were investigated. The genetic polymorphism analysis was performed using a DNA ABI PRISM™ 377 sequence detection system (Applied Biosystems) in 135 sporadic breast cancer cases. Results: The distribution of the genotypes of the A46922G polymorphism of Ku70 in patients differed significantly (p < 0.05) from those predicted by the Hardy-Weinberg equilibrium. There were significant differences in the frequencies of alleles between the breast cancer subjects and controls (p 0.05) from that predicted by the Hardy-Weinberg distribution. Conclusion: The results support the hypothesis that the A46922G polymorphism of the Ku70 gene may be associated with the incidence of breast cancer in women from the Lodz region of Poland.